Seleção de bactérias láticas com atividade anti-Listeria a partir de leite de cabra cru - Silva, Liliane Andrade da (2014)
Lactic acid bacteria can produce bacteriocins and have been explored for applications as natural preservatives in foods. Bacteriocins are peptides and proteins with antimicrobial activity and can inhibit the growth of pathogenic bacteria such as Listeria monocytogenes and other spoilage microorganisms. L. monocytogenes can be present in many types of food due to its ability to survive in a wide temperature range, and causes listeriosis by ingestion of contaminated food. This study aimed at the isolation and identification of lactic acid bacteria (LAB) with bacteriocinogenic potential, the characterization of the cell-free supernatants (CFS) regarding: the antimicrobial activity; the spectrum of action; thermal stability and at different pHs; resistance to chemicals and NaCl concentrations; the mode of action of the bacteriocins produced; the adsorption capacity to the target cells in different temperatures, pH and concentrations of chemicals and NaCl; perform the molecular identification of the LAB. Three strains (LS1, LS2 and LS3) bacteriocinogenic of raw goat's milk with anti-listeria activity were isolated. In particular Lactococcus lactis (LS2), which produced bacteriostatic, active bacteriocin at low pH and 4 ° C to 80 ° C, which can be an alternative for the control of Listeria in fermented dairy products.